Pengaruh Lingkungan Kerja Fisik dan Motivasi Kerja terhadap Kinerja Karyawan pada PT Pancaran Indonesia Kabupaten Tangerang - Raudatul Janah; Fahmi Susanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to determine the effect of the physical work environment and work motivation on the performance of employees of PT Pancaran Indonesia Kabupaten Tangerang, Depok City, both partially and simultaneously. The method used is a quantitative method with a causal associative approach and probability sampling technique with a sample of 82 and processed using SPSS 25. Data analysis using validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of the study show that the physical work environment has a value of tcount > ttable or (3,714 > 1.994). Work motivation has a tcount > ttable or (11,852 > 1.994). The physical work environment and work motivation have Fcount > Ftable or (72, 865 > 2,737). This is also reinforced by the ρ value < Sig.0.05 or (0.000 <0.05). there is a significant effect simultaneously between the physical work environment (X1) and work motivation (X2) on employee performance (Y) with a contribution of 67,9% while the remaining 32,1% is influenced by other factors outside this study. The multiple linear regression equation Y = 5,949 + 0,067X1 + 0,985X2 + e.